TARGETING KNOWLEDGE, BARRIERS, AND FACILITATORS TO PARTICIPATION IN DEMENTIA RESEARCH (THE POWER PROJECT). (20th December 2022) - Sajatovic, Martha; Herrmann, Lynn; Knebusch, Clare; Sarna, Kaylee; Lerner, Alan; Fuentes-Casiano, Edna; Burant, Christopher
Abstract: Racial and ethnic minorities are under-represented in dementia research. We tested a conceptually-driven health communication approach targeting evidence-based barriers and facilitators to research participation vs. dementia awareness training. Input from the minority advisory board (MAB) of the Cleveland Alzheimer's Disease Research Center (CADRC) informed development of 2 brief health communication videos which differentially focused on research barriers and facilitators (POWER) versus an education control (EDU). A randomized controlled on-line survey compared POWER vs. EDU among 200 individuals ≥ 50 years. We examined pre/post video change in research motivation measured by the transtheoretical model, dementia knowledge and cumulative barriers and facilitators. Interim analysis included 129 individuals who completed the pre-video survey, mean age 58.8 (SD 14.9), 101 (78.3 %) women, 54 (41.9 %) non-white. 100 (77.5 %) completed the post-video survey. Whole sample dementia knowledge improved from pre (mean 4.6, SD 1.3) vs. post (5.8, SD 0.7) video (p <.01), as did facilitators to research from pre (22.4, SD 2.7) vs. post (22.8, SD 3.0) video (p=.02), while there was no significant change in barriers. Research motivation was increased pre (10.8, SD 2.0) vs. post (22.8, SD 3.0) video (p=.02). Overall, dementia knowledge improved more with EDU vs. POWER (p=.04). African-American participants trended towards greater improvement in dementia knowledge with EDU vs. POWER (p=.07), while non-African-Americans had greater facilitator improvement with POWER vs. EDU (p=.03). Targeted communication approaches that address knowledge gaps and both barriers and facilitators to participation may improve engagement of diverse groups in dementia research.